Developing friction stir spot welding windows for dissimilar AL5083 and C10100 joints. (2017) - Siddharth, S.; Senthilkumar, T.
In this investigation, process operation limit diagrams in the form of friction stir spot welding windows for obtaining good quality friction stir spot joints were attempted using dissimilar combinations of aluminium Al 5083 and copper C10100. By varying the important process parameters such as tool rotational speed, plunge depth and dwell time, tool rotational speed-dwell time and tool rotational speed-plunge depth diagrams were constructed, considering the joint quality aspect, extent of flash formation, width and depth of keyhole, its tensile strength and interface hardness. Tensile properties of the joints were evaluated using lap shear tensile tests. Vickers micro hardness tester was used to evaluate interface hardness. Validation experiments proved that, the joints made by selecting process parameter values within the two windows, had higher strength and reduced interface hardness. These windows would act as reference maps for selection of appropriate parameters for strong joints.